The effect of ursodeoxycholic acid on the relative expression of the lipid metabolism genes in mouse cholesterol gallstone models - Fan, Ning (Lipids Health Dis, 2020)
BACKGROUND: Many studies indicate that gallstone formation has genetic components. The abnormal expression of lipid-related genes could be the basis for particular forms of cholesterol gallstone disease. The aim of this study was to obtain insight into lipid metabolism disorder during cholesterol gallstone formation and to evaluate the effect of ursodeoxycholic acid (UDCA) on the improvement of bile lithogenicity and its potential influence on the transcription of lipid-related genes. METHODS: Gallstone-susceptible mouse models were induced by feeding with a lithogenic diet (LD) for 8 weeks. Bile and liver tissues were obtained from these mouse models after 0, 4 and 8 weeks. Bile lipids were measured enzymatically, and the cholesterol saturation index (CSI) was calculated to evaluate the bile lithogenicity by using Carey’s critical tables. Real-time polymerase chain reaction (RT-PCR) was used to detect the mRNA expression levels of farnesoid X receptor (FXR), liver X receptor (LXR), adenosine triphosphate-binding cassette subfamily G member 5/8 (ABCG5/8), cholesterol 7-α hydroxylase (CYP7A1), oxysterol 7-α hydroxylase (CYP7B1), sterol 27-α hydroxylase (CYP27A1), peroxisome proliferator-activated receptor alpha (PPAR-α) and adenosine triphosphate-binding cassette subfamily B member 11 (ABCB11). RESULTS: The rate of gallstone formation was 100% in the 4-week group but only 30% in the UDCA-treated group. The UDCA-treated group had a significantly lower CSI compared with other groups. Of special note, the data on the effects of UDCA showed higher expression levels of ABCG8, ABCB11 and CYP27A1, as well as lower expression levels of LXR and PPAR-α, compared to the model control group. CONCLUSIONS: UDCA exhibits tremendously potent activity in restraining lipid accumulation, thus reversing the lithogenic effect and protecting hepatocytes from serious pathological damage. The abnormal expression of ABCG8, CYP7A1, CYP27A1, LXR and PPAR-α might lead to high lithogenicity of bile. These results are helpful in exploring new lipid metabolism pathways and potential targets for the treatment of cholesterol stones and for providing some basis for the study of the pathogenesis and genetic characteristics of cholelithiasis. Research on the mechanism of UDCA in improving lipid metabolism and bile lithogenicity may be helpful for clinical treatment and for reducing the incidence of gallstones.